ANALISIS PENERAPAN PENGALIHAN HAK TAGIH PADA PT BAMBANG DJAJA DAN PT HAVANNA TEGUH PERTIWI DALAM PUTUSAN 08/PDT.SUSPKPU/2020/PN.NIAGA.JKT.PST - Rehulina Dianingwati; Atalim Atalim (Fakultas Hukum Universitas Tarumanagara, 2021)
The transfer of claim rights is regulated in the Civil Code. Article 613 paragraph (1) of the Civil Code contains regulations regarding things that must be done in committing violations. In this case, PKPU I Petitioners and PKPU II Petitioners feel that the PKPU Respondent has been harmed because the PKPU Respondent is not subject to debt until maturity. Bankruptcy and Suspension of Payment Obligation (PKPU) Respondents always have good intentions to pay their debts to PKPU I Petitioners and PKPU II Petitioners even though the time has passed. However, there is a cessie in the settlement of this PKPU so that the Legal Consultants of the PKPU I Petitioners and PKPU II Petitioners indirectly become third parties in this case where the status is questionable. By using a cessie in this case, it will indirectly lead to simplicity in this case and the PKPU Respondent's danger because the debtor can default.